PERANCANGAN TATA LETAK ULANG GUDANG TEMBAKAU PADA WAREHOUSE PRIMARY DI PT ALCOTRAINDO BATAM - Hosea, Hosea Frans Dito Sihombing; Prakasa hasibuan, Rizki (LPPM Universitas Putera Batam, 2023)
This study discusses the re-layout design of the tobacco warehouse on primary warehouse at PT. Alcotraindo Batam. The problems in the primary warehouse are that the placement isn’t optimal. The stages of the research started from calculating the frequency of movements, classifying goods, determining the amount of storage and making a proposed layout by adding shelves to the loose pack area and changing shape of the box arrangement to pallets. The results of this study found that the frequency movement, goods were grouped into class A which contained 2 items of goods, class B which contained 7 items of goods, and class C which contained 137 items of goods. By applying the proposed layout to increase warehouse capacity, only 146 locations out of 204 available locations are used in the primary store.It has empty locations to put 58 location areas or 303 large pallets and 126 small pallets. The remaining locations are used in case of an increase in demand for goods. The previous layout capacity was 649 pallets and the proposed layout capacity was 1078 pallets. The storage capacity of goods in the primary store increased by 39.8%.